Bahasa dan Peran Semiotika Dalam Studi Agama - Musyarofah, Anna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Language as a tool used by a person to express thoughts, feelings, desires and actions is a sign that has meaning. Language that is not separate from human life can take the form of spoken or written forms. Oral and written language can be understood and analyzed from various points of view, one of which is the semiotic approach in which this science is used to express the sign or symbol in question. Language is not only limited to social life, but also in religious studies, language is often found as a certain sign or symbol. Thus, semiotics is one of the right sciences to express the meaning of language so as not to create only partial and contextual understandings so that religion does not become an opening for debates and disputes because it differs in understanding the meaning of language. This is aimed at realizing religion as rahmatan lil 'alamin not only as a symbol but also a reality in social life.